Uma abordagem sobre a teoria dos grafos no ensino médio - Pereira Junior, Antonio Valdemir (2018)
The present work aims to suggest an approach on the teaching of graphs in high school, especially for second year classes, given the ease that the students present to handle current technological instruments; to arouse students' interest in mathematics from certain terrestrial navigation applications, considering that this instigates them to check intrinsic mathematics in other applications; to induce the problematization to facilitate the learning of this content by the students. For this purpose, the bibliographic research was used as a method for collecting data, through the study verified in the theoretical reference on the approach of graphs in high school and the case study, using as data collection instruments some exercises and experiments made available in the project, which were applied in the EEFM Professor Edmilson Guimarães de Almeida. From the data analysis it was possible to verify the relevance of giving students access to the technologies, since the characteristics of the Matrixcal and the terrestrial navigation application were cited by them as one of the most important instruments to facilitate the obtaining of results that, if calculated manually, would require a lot of effort and time. The technological material of the school, like the computer laboratory, presented itself as a great challenge in the execution of some tasks. Finally, based on the study carried out and on the results obtained, it was possible to confirm that the study on graphs can lead to the development of some abilities that are sometimes inert in the students, such as capacity for innovation, recreation from the known, adaptability to the new, creativity, autonomy and communication.